Analisis Kualitas Sistem Informasi Absensi Karyawan dengan Metode McCall - Khairul, Khairul Zaman; Rianti, Eva; Yenila, Firna; Pradana, Taufan (Jurnal KomtekInfo, 2023)
Testing the quality of the employee attendance information system that has been built can be developed for use in the management process in an organization. System testing is used to ensure that the information system being built can run according to requirements. This research aims to analyze the quality of the information system on the performance of the employee absence process. The analytical method used adopts the McCall performance method to examine the extent to which the attendance system can be productive in dealing with employee absenteeism problems. The McCall method has performance in identifying various aspects of information system quality such as reliability, efficiency, ease of use. There are measurement indicators such as correctness, usability, integrity, reliability and efficiency. Based on the results of the analysis produced by the McCall method, the information system quality results provide a positive response to the reliability factor with a percentage of 80.88%, correctness 79.6%, usability 70.6% while integrity 64.6% and efficiency 46.2%. The results of this analysis can be carried out in an accumulation testing process on all factors with a Likert scale of 82.2%. Based on these results, this research can provide a contribution to maximizing system performance as well as recommendations for improvements to the employee attendance information system.